1987
DOI: 10.1128/jcm.25.7.1143-1147.1987
|View full text |Cite
|
Sign up to set email alerts
|

Two-year survey of etiologic agents of diarrheal disease at San Lazaro Hospital, Manila, Republic of the Philippines

Abstract: The prevalence of bacterial pathogens and rotavirus in 2,908 patients with diarrhea who were admitted to San Lazaro Hospital in Manila in 1983 and 1984 was determined. One or more enteric pathogens were isolated or detected in samples from 1,698 (58.4%) patients. Isolation rates for the various enteropathogens were as follows: rotavirus, 30.6%; Shigella spp., 11.6%; Salmonella spp., 9.2%; enterotoxigenic Escherichia coli (1983 only), 7.8%; Vibrio cholerae biotype eltor, 3.8%; non-Ol V. cholerae, 2.8%; Vibrio p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 18 publications
3
44
2
Order By: Relevance
“…The percentage of occurrence of Rota virus was not more in the children under two years of age in our study. This is in contrast to the results from other countries, where Rota virus was significantly higher in children being less than two years of age (1,23,25,35).…”
Section: Distribution Of Enteropathogens According To Agecontrasting
confidence: 99%
See 1 more Smart Citation
“…The percentage of occurrence of Rota virus was not more in the children under two years of age in our study. This is in contrast to the results from other countries, where Rota virus was significantly higher in children being less than two years of age (1,23,25,35).…”
Section: Distribution Of Enteropathogens According To Agecontrasting
confidence: 99%
“…The prevalence and relative frequency reported from Bangladesh and South Africa was between 1522% (43,44). The recovery rate in our study using correct technique (12 %) was comparable with those reported from other countries such as Hong Kong, Egypt and Phillipines (25,40,41), which was in the range of Initially, Butzler's and Skirrow's medium (16,17) were utilized for the isolation of Campylobacter. The rate in our study increased from 1.6% to 12% after the improvement of isolation technique, by using the new Blood-Free-Selective medium during the last two years of the study (18, 45 46).…”
Section: Frequency Isolation Of Carnpylobactersupporting
confidence: 82%
“…Other pathogens of importance in adults were Salmonella spp. and Vibrio parahaemolyticus (rarely isolated from children under 5 years old) [6]. In this study, only one infant was found to have V. parahaemolyticus.…”
Section: Discussionmentioning
confidence: 51%
“…Aeromonas has been recognized as a human enteropathogen since around 1970 (3). Investigators have increasingly directed their attention to Aeromonas in recent years because of the high frequency of disease with a variety of symptoms (2,15,20,24). The isolation rate of this relatively new enteropathogen from diarrheal stools has varied from report to report, such as 33% in Bangladesh (15), 1 to 2% in the Philippines (2), about 10% in the U.S.A. and Japan (20,24), 30 to 50% in Peru (25), etc.…”
mentioning
confidence: 99%